Influencing public health without authority - K Suresh (Wolters Kluwer Medknow Publications, 2012)
This paper analyzes the present processes, products and needs of post-graduate public health education for the health programming, implementation and oversight responsibilities at field level and suggests some solutions for the institutes to adopt or adapt for improving the quality of their scholars. Large number of institutions has cropped up in India in the recent years to meet the growing demand of public health specialists/practitioners in various national health projects, international development partners, national and international NGOs. Throwing open MPH courses to multi-disciplinary graduate's is a new phenomenon in India and may be a two edged sword. On one hand it is advantageous to produce multi-faceted Public health postgraduates to meet the multi tasking required, on the other hand getting all of them to a common basic understanding, demystifying technical teaching and churning out products that are acceptable to the traditional health system. These Institutions can and must influence public health in the country through producing professionals of MPH/ MD degree with right attitude and skill-mix. Engaging learners in experimentation, experience sharing projects, stepping into health professionals' roles and similar activities lead to development of relatively clear and permanent neural traces in the brain. The MPH institutes may not have all efficient faculties, for which they should try to achieve this by inviting veterans in public health and professionals from corporate health industry for interface with students on a regular basis. The corporate and public health stalwarts have the capacities to transmit the winning skills and knowledge and also inspire them to adopt or adapt in order to achieve the desired goals.